(untitled) (KMC Journal, 2024)
Noise pollution is one of the major environmental threats that highly affects human livelihood. This study aims to assess the noise level near educational institutions located in Dhangadhi Sub-Metropolitan City. Eighteen schools were chosen for this study. The noise level was recorded in those schools in the school time (10:00-16:00). For measurement, time was categorized into three parts viz. 10:00-12:00; 12:00-14:00; and 14:00-16:00. The noise level was measured using a digital sound level meter in the month of February 2024. The result shows that the noise level () measured at different locations is above the prescribed standard value of noise level. Among the selected institutions, the noise level was higher in those schools which are near the roads. The institutions that are little inside the road are less noisy. This study reveals that the noise pollution in the respective institutions is due to high traffic of vehicles, bad condition of road, human crowd, unnecessary use of horns, etc.